Exchange Economies and Loss Exposure: Experiments Exploring Prospect Theory and Competitive Equilibria in Market Environments - Myagkov, Mikhail; Plott, Charles R. (American Economic Review, 1997)
Exchange economies were created in which individuals faced losses. If people are risk seeking in the losses, as predicted by prospect theory, then due to the nonconvexity, the competitive equilibria are all on the boundaries of the Edgeworth Box. The experimental results are that risk-seeking behavior is observed in many people and appears in markets as predicted. In addition, market behavior is consistent with answers to hypothetical questionnaires. Contrary to prospect theory, risk seeking seems to diminish with experience; preferences in the market setting are not labile; and risk-seeking preferences are not simply a result of framing effects.